(untitled) (Global Journal of Management and Business Research, 2018)
A key challenge facing organizations is how to encourage employees to engage in proenvironmental behaviors. Workplace spirituality has been conceptualized as offering new insights into how individuals experience a deeper level of intrinsic work motivation and engagement. Based on a survey of 349 nurses, we found that workplace spirituality was significantly associated with nurses’ pro-environmental behavior and that employee engagement indirectly affects the relationship between workplace spirituality and pro-environmental behavior. The results suggest that environmental awareness moderated the effect of workplace spirituality on pro-environmental behavior of nurses. Managers of nursing services should consider workplace spirituality and its positive influence on nurses’ outcomes in order to improve their performance and, subsequently, the healthcare system.